Experimental investigation on high temperature wettability and structural behaviour of SAW fluxes using MgO–TiO2–SiO2 and Al2O3–MgO–SiO2 flux system. Issue 5 (1st April 2020) - Sharma, Lochan; Kumar, Jagdish; Chhibber, Rahul
Abstract: To establish the relationship between wettability and structure with the change in SAW flux composition, the contact angle measurement study was performed at 1700 K. For MgO–TiO2 –SiO2 and Al2 O3 –MgO–SiO2 flux system the wetting behaviour was studied by evaluating the contact angle as well as surface tension properties. Sessile drop method was used to determine the wetting properties of SAW fluxes. Twenty-one SAW fluxes were designed & developed by applying mixture design approach of design of experiments. Chemical, phase and structural properties of SAW fluxes were measured using modern techniques such as X-ray fluorescence (XRF), X-ray diffraction (XRD) & Fourier Transform Infra-red spectroscopy (FTIR). As per the calculated contact angle value, different surface tension values for MgO–TiO2 –SiO2 and Al2 O3 –MgO–SiO2 flux system was calculated using Young's & Boni's equations. Using Dupre's equation the adhesion energy for twenty-one basic fluxes was also calculated. Measured contact angle value increased with increase in the TiO2 /MgO & TiO2 /Al2 O3 flux ratio. Lower contact angle gives higher wettability between the flux and the heating substrate. With increase of TiO2 /SiO2 ratio up to 1.5 to 2.0 the calculated surface tension value is decreasing while after that it is increased with increase in TiO2 /SiO2 ratio.